The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1002/14651858.cd008983.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Influenza vaccines in immunosuppressed adults with cancer

Abstract: and the ImmunoCompromised (UNIIC) Study Group. Influenza vaccination for immunocompromised patients: systematic review and meta-analysis by etiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
94
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(107 citation statements)
references
References 96 publications
1
94
0
6
Order By: Relevance
“…Bacterial infections and viral reactivations are well-known complications of neutropenia and lymphopenia, but it is less clear to what extent the severity of de novo viral infections is also affected. Although there are data suggesting that chemotherapy-treated patients with cancer are at risk for severe complications of influenza 6,7 , it is unclear how this might generalize to COVID-19. A recent study has reported increased incidence and morbidity of COVID-19 in patients with cancer 8 , but those findings were rightly challenged by others 9,10 .…”
Section: Clinical Activitiesmentioning
confidence: 99%
“…Bacterial infections and viral reactivations are well-known complications of neutropenia and lymphopenia, but it is less clear to what extent the severity of de novo viral infections is also affected. Although there are data suggesting that chemotherapy-treated patients with cancer are at risk for severe complications of influenza 6,7 , it is unclear how this might generalize to COVID-19. A recent study has reported increased incidence and morbidity of COVID-19 in patients with cancer 8 , but those findings were rightly challenged by others 9,10 .…”
Section: Clinical Activitiesmentioning
confidence: 99%
“…Our primary outcome combined influenza hospitalisations and deaths but was dominated by the former; it is plausible that there may be a lower threshold for hospitalisation in cancer survivors which could have exaggerated the difference in risk of the primary outcome between cancer survivors and controls, but is unlikely to fully explain the large associations we observed. Finally, we had some missing data on smoking and BMI data, and we excluded those with missing data from the analysis; this is unlikely to affect our findings under the Improving influenza vaccination coverage among cancer survivors should be a priority, as the vaccine is both effective and safe 29,30 but coverage has been reported in the range of 50% to 76% among cancer survivors in the US and in the UK. 31,32 Immunisation for streptococcus pneumoniae may also be considered.…”
Section: Discussionmentioning
confidence: 99%
“… 36 37 A Cochrane meta-analysis also found vaccinated cancer patients had a significantly lower all-cause mortality than those who did not get vaccinated. 3 However, despite public health recommendations, the documented rates of vaccination are only 30% to 50% among patients with cancer, similar to the general population. 38 39 In contrast to their relatively low vaccination rates, proactive education approaches that raise awareness about the necessity of vaccination among cancer patients is warranted.…”
Section: Discussionmentioning
confidence: 99%